Facile Synthesis of a 3,4-Ethylene-Dioxythiophene (EDOT) Derivative for Ease of Bio-Functionalization of the Conducting Polymer PEDOT - Wu, Bingchen; Cao, Bin; Taylor, Ian Mitch; Woeppel, Kevin; Cui, Xinyan Tracy (Frontiers in Chemistry, 2019)
In the pursuit of conducting polymer based bio-functional devices, a cost-effective and high yield synthesis method for a versatile monomer is desired. We report here a new synthesis strategy for a versatile monomer 2-methylene-2,3-dihydrothieno (3,4-b) (1,4) dioxine, or 3,4-ethylenedioxythiophene with a exomethylene side group (EDOT-EM). Compared to the previously reported synthesis route, the new strategy uses less steps, with faster reaction rate, and higher yield. The presence of EM group opens up endless possibility for derivatization via either hydro-alkoxy addition or thiol-ene click chemistry. EDOT-EM could be polymerized into stable and low impedance PEDOT-EM polymer using electro-polymerization method on different conducting substrates at both macro and micro scales. Facile post-functionalization of PEDOT-EM with molecules of varying size and functionality (from small molecules to DNAs and proteins) was achieved. The new synthetic route of EDOT-EM and the ease of post-functionalization of PEDOT-EM will greatly accelerate the use of conducting polymer in a broad range of organic electronics and bioelectronics applications.